KINERJA BADAN KEPEGAWAIAN DAERAH DALAM MENINGKATKAN PRESTASI KERJA APARATUR PEMERINTAH KABUPATEN HALMAHERA UTARA - Hi Hasan, Muhammad (Aksara Public, 2019)
In RI Law No. 43/1999 concerning Personnel Principal stated that: In order to achieve the National Goals and realize a social society that is aware of the law, adapted, democratic, prosperous, fair and moral, required Public Servants who serve as public servants who deliver services in a fair and equitable, maintain the unity and integrity of the nation with full loyalty to the Pancasila and the 1945 Constitution. the quality of Civil Servants in the Government of North Halmahera Regency in general is still limited in the sense that some still do not understand the main tasks and functions, the lack of the ability of the apparatus to carry out technology. given the importance of the quality of Civil Servants Resources in the implementation of development, government, and community service is demanded to always strive to improve employee work performance, this study discusses the performance of the District Personnel Agency. North Halmahera in improving work performance. From the results of the research in the field, there have been BKD efforts to improve the performance of its employees.